Unique nonclinical safety profile of PF-06835919, a ketohexokinase inhibitor, highlights a species-dependent mechanism - Jun Zhou; Christopher Houle; Frank J. Geoly; Sarah N. Campion; Jon Cook (Regulatory Toxicology and Pharmacology, 2026)

Thyroid dysregulation underlies altered ovarian cyclicity in rats exposed to PF-06835919, a ketohexokinase inhibitor - Sarah N. Campion; Christopher J. Bowman; Christopher Houle; Jessie Qian; Jun Zhou; Jon Cook (Reproductive Toxicology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Collaborative evaluation of in silico predictions for high throughput toxicokinetics - John F. Wambaugh; Nisha S. Sipes; Gilberto Padilla Mercado; Jon A. Arnot; Linda Bertato; Trevor N. Brown; Nicola Chirico; Christopher Cook; Daniel E. Dawson; Sarah E. Davidson-Fritz; Stephen S. Ferguson; Michael-Rock Goldsmith; et al. (Toxicology in Vitro, 2026)

Developing Economic Policy Instruments for Tourism Management in Protected Areas - Jukka Siltanen; Jon Geir Petursson; David Cook; Brynhildur Davidsdottir (Environmental Management, 2026)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Marine protected areas and fishing community well-being: An example from statewide socioeconomic monitoring of the California MPA network - Samantha Cook; Laurie Richmond; Joice Chang; Kelly Sayce; Jon Bonkoski; Cheryl Chen; Jocelyn Enevoldsen; Rachelle Fisher; Denise Chin; Mikayla Kia (Ocean & Coastal Management, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Absence of functional deficits in rats following systemic administration of an AAV9 vector despite moderate peripheral nerve and dorsal root ganglia findings: A clinically silent peripheral neuropathy - Cheryl Tyszkiewicz; Seo-Kyoung Hwang; Jamie K. DaSilva; Ramesh C. Kovi; Kelly A. Fader; Madhu P. Sirivelu; June Liu; Chris Somps; Jon Cook; Chang-Ning Liu; Helen Wang (NeuroToxicology, 2024)

Factors Influencing Health-Related Quality of Life of Patients with Spinocerebellar Ataxia - Niklas Weber; Maresa Buchholz; Anika Rädke; Jennifer Faber; Tanja Schmitz-Hübsch; Heike Jacobi; Thomas Klockgether; Wolfgang Hoffmann; Bernhard Michalowsky; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; et al. (The Cerebellum, 2024)
Background Little is known about the progression of health-related quality of life (HRQoL) and predicting factors in spinocerebellar ataxia (SCA). Such knowledge is crucial to identify modifiable factors promoting everyday life with SCA and attenuating HRQoL decline. Objectives This study is to assess HRQoL progression and identify factors affecting SCA patients’ HRQoL. Methods Longitudinal data (three-year follow-up) of 310 SCA patients of the European SCA3/Machado-Joseph-Disease Initiative (ESMI) (2016-2022) and 525 SCA patients (SCA1, SCA2, SCA3 or SCA6) of the EUROSCA natural history study cohort (2006–2015) were assessed. Both large cohort studies share standardized assessments of clinical measures, SARA, INAS, PHQ-9, and HRQoL (EQ-5D-3L). The association between HRQoL and clinical measures was assessed by Spearman Correlation (r s ). Multivariable panel regression models were performed to evaluate the impact of patients’ socio-demographics, age of onset, SCA type and body mass index (BMI), and clinical measures on HRQoL progression. Results HRQoL significantly decreased over one (− 0.014, p = 0.095), two (− 0.028, p = 0.003), and three years (− 0.032, p = 0.002). Ataxia severity and mental health strongly correlated with HRQoL (r s SARA = − 0.589; r s PHQ-9 = − 0.507). HRQoL more intensively declined in male (ß = − 0.024, p = 0.038) patients with an earlier age of onset (ß = 0.002, p = 0.058). Higher progression of ataxia severity (ß = − 0.010, p ≤ 0.001), mental health problems (ß = − 0.012, p < 0.001), and higher BMI (ß = − 0.003, p = 0.029) caused more severe decline of patients’ HRQoL over time. Discussion In absence of curative treatments, stronger focus on mental health and weight influence could help clinical evaluation and accompany treatment improving SCA patients’ HRQoL, especially in male patients with early disease onset.

Development of an open-source carbon footprint calculator of the UK craft brewing value chain - Alexander L. Bowler; Sarah Rodgers; Fanran Meng; Jon McKechnie; David J. Cook; Nicholas J. Watson (Journal of Cleaner Production, 2024)

Health-Related Quality of Life in Patients with Spinocerebellar Ataxia: a Validation Study of the EQ-5D-3L - Maresa Buchholz; Niklas Weber; Anika Rädke; Jennifer Faber; Tanja Schmitz-Hübsch; Heike Jacobi; Feng Xie; Thomas Klockgether; Bernhard Michalowsky; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; et al. (The Cerebellum, 2023)
Although health-related quality of life (HRQoL) has developed into a crucial outcome parameter in clinical research, evidence of the EQ-5D-3L validation performance is lacking in patients with spinocerebellar ataxia (SCA) types 1, 2, 3, and 6. The objective of this study is to assess the acceptability, validity, reliability, and responsiveness of the EQ-5D-3L. For n = 842 predominantly European SCA patients of two longitudinal cohort studies, the EQ-5D-3L, PHQ-9 (Patient Health Questionnaire), and ataxia-specific clinical assessments (SARA: Scale for Assessment and Rating of Ataxia; ADL: activities of daily living as part of Friedreich’s Ataxia Rating Scale; INAS: Inventory of Non-Ataxia Signs) were assessed at baseline and multiple annual follow-ups. The EQ-5D-3L was evaluated regarding acceptability, distribution properties, convergent and known-groups validity, test-retest reliability, and effect size measures to analyze health changes. The non-item response was low (EQ-5D-3L index: 0.8%; EQ-VAS: 3.4%). Ceiling effects occurred in 9.9% (EQ-5D-3L) and 3.0% (EQ-VAS) with a mean EQ-5D-3L index of 0.65 ± 0.21. In total, convergent validity showed moderate to strong Spearman’s rho ( r s > 0.3) coefficients comparing EQ-5D-3L and EQ-VAS with PHQ-9, SARA, ADL, and INAS. EQ-5D-3L could discriminate between groups of age, SARA, ADL, and INAS. Intra-class correlation coefficients (EQ-5D-3L ICC : 0.95/EQ-VAS ICC : 0.88) and Kappa statistics (range 0.44 to 0.93 for EQ-5D-3L items) indicated tolerable reliability. EQ-5D-3L shows small (effect size < 0.3) to moderate (effect size 0.3–0.59) health changes regarding ataxia severity. The analysis confirms an acceptable, reliable, valid, and responsive recommended EQ-5D-3L in SCA patients, measuring the HRQoL adequately, besides well-established clinical instruments.

Evaluating economic impacts of protected areas in contexts with limited data; the case of three national parks in Iceland - Jukka Siltanen; Jon Geir Petursson; David Cook; Brynhildur Davidsdottir (Journal of Environmental Management, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Investigating slow-moving shallow soil landslides using Sentinel-1 InSAR data in Gisborne, New Zealand - Matthew E. Cook; Martin S. Brook; Ian J. Hamling; Murry Cave; Jon F. Tunnicliffe; Rachel Holley (Landslides, 2023)
Landslides are widespread geomorphological features on the North Island of New Zealand, where they represent one of the primary landscape-forming processes. This study focuses on the steepland terrain surrounding Gisborne, a city located on the east coast of the North Island, at the Hikurangi subduction margin. This terrain consists of young, weak, sedimentary rocks and soils; the most common modes of slope failures are soil creep, slides and flows in shallow, clay-rich soil and regolith, triggered by heavy rainfall. Based on observational data from Sentinel-1 imagery, this study leverages results from interferometric synthetic aperture radar (InSAR) processing to reveal the distribution of deformation across Gisborne’s steepland periphery from January 2016 to December 2021. Velocities in the line of sight were obtained from the stack of interferograms and projected along the direction of maximum slope, to extract the true displacement on the slopes. The ascending and descending data sets were combined to reveal the vertical and horizontal components of the deformation. The results were combined with a regional LiDAR data set, aerial imagery and field observations to delineate areas of slope deformation. Finally, slope deformation time series data was compared with rainfall records to identify seasonal changes, due to shrinking and swelling of expansive soils. Although the InSAR displacement data contains some noise, results could be used to identify 132 unstable slopes within the study area, caused by soil creep and earthflows. Also, the shrink-swell of expansive soils causes a seasonal pattern of displacements, which varied by 10–20 mm/year between Austral winter and summer, strongly correlated to rainfall.

Engineering geomorphological and InSAR investigation of an urban landslide, Gisborne, New Zealand - Matthew E. Cook; Martin S. Brook; Ian J. Hamling; Murry Cave; Jon F. Tunnicliffe; Rachel Holley; David J. Alama (Landslides, 2022)
The East Coast region of New Zealand has some of the highest erosion rates in the world, due to its proximity to an active plate boundary, susceptibility to high-intensity storms and steep terrain underlain by young soft sedimentary rock and soil. In the city of Gisborne, expansion of residential blocks into steeper terrain in peri-urban areas has required improved capacity for the characterisation and monitoring of slope stability. Landslides have affected several properties and have destroyed infrastructure. Slope failure commonly occurs during heavy rainfall events when slow-moving retrogressive slides transition into earthflows and mudflows. In this study, we used in situ sampling and testing methods combined with remote sensing techniques to provide an understanding of the pre-failure and post-failure behaviour of an urban landslide in Gisborne. High-resolution aerial imagery, unmanned aerial vehicle imagery and light detection and ranging data revealed slope morphology and contours of prehistoric failures in the area, and highlighted the more recent impacts of deforestation on slope stability. Furthermore, Sentinel-1 InSAR analysis determined that gradual deformation began in 2017, following two ex-tropical cyclone events. Deformation downslope continued until an initial failure in July 2020. Following that event, some parts of the slope proceeded to accelerate, leading to a further reactivation event in November 2021, following heavy rainfall. During this November 2021 event, average line of sight velocities ranged from −7.9 to −11.2 mm/year, and deformation rates in the vertical direction (related to rotational slumping) averaged −11.2 to −11.9 mm/year, consistent with field observations.

The Open-Ocean Gulf of Mexico After Deepwater Horizon: Synthesis of a Decade of Research - Tracey T. Sutton; Rosanna J. Milligan; Kendra Daly; Kevin M. Boswell; April B. Cook; Maëlle Cornic; Tamara Frank; Kaitlin Frasier; Daniel Hahn; Frank Hernandez; John Hildebrand; Chuanmin Hu; et al. (Frontiers in Marine Science, 2022)
The scale of the Deepwater Horizon disaster was and is unprecedented: geographic extent, pollutant amount, countermeasure scope, and of most relevance to this Research Topic issue, range of ecotypes affected. These ecotypes include coastal/nearshore, continental shelf, deep benthic, and open-ocean domains, the last of which is the subject of this synthesis. The open-ocean ecotype comprises ~90% of the volume of the Gulf of Mexico. The exact percentage of this ecotype contaminated with toxins is unknown due to its three-dimensional nature and dynamics, but estimates suggest that the footprint encompassed most of its eastern half. Further, interactions between the water column and the deep benthos may be persistent, making this synthesis one of time (a decade) rather than event conclusion. Here we examine key elements of the open-ocean ecosystem, with emphasis on vulnerability and resilience. Of paramount importance relative to the Gulf nearshore and shelf ecotypes, pre-disaster baseline data were lacking for most of the fauna. In such cases, inferences were drawn from post-disaster assessments. Both phytoplankton and mesozooplankton vulnerabilities were quite high, but resilience appeared equally so. The phytoplankton situation was a bit more complex in that toxin-imposed reductions may have been offset by nutrient injection via high freshwater discharge in 2010. Intermediate trophic levels exhibited population-level depressions, ostensibly due to high vulnerability and low resilience. Apex predator impacts were variable. Certain large epipelagic fishes may have avoided the highest concentrations of hydrocarbons/dispersant, and thus larval abundances returned to pre-disaster levels of variability and abundance within a few years after a steep initial decline. Oceanic cetaceans, particularly shallow-diving stenellid dolphins, did not appear to avoid oiled waters and exhibited strong declines in the northern Gulf. Given that population declines of many open-ocean taxa appear to be ongoing a decade later, we conclude that this largest of Gulf ecosystem components, like its deep-benthic counterpart, is as fragile as it is voluminous. This is particularly concerning given the rapid, and likely irreversible, shift to deeper waters by the US and Mexican oil industries in concert with the higher likelihood of accidents with increasing platform depth.

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

Hiding in Plain Sight: Elopomorph Larvae Are Important Contributors to Fish Biodiversity in a Low-Latitude Oceanic Ecosystem - Jon A. Moore; Dante B. Fenolio; April B. Cook; Tracey T. Sutton (Frontiers in Marine Science, 2020)

Switchgrass for forage and bioenergy: harvest and nitrogen rate effects on biomass yields and nutrient composition - John A. Guretzky; Jon T. Biermacher; Billy J. Cook; Maru K. Kering; Jagadeesh Mosali (Plant and Soil, 2011)